COVİD-19 Akut Respiratuvar Distres Sendromu Fenotiplerinde Mekanik Ventilasyon - Özgür Kömürcü; Sercan Küllaç; Abdurrahman Yılmaz; Fatma Ülger (Galenos Yayinevi, 2022)
Objective: Coronavirus disease-2019 (COVID-19)-related acute respiratory distress syndrome (ARDS) phenotypes in lung compliance have been described in patients with COVID- 19-related ARDS. Our study examined mechanical ventilation support and its results in patients with COVID-19-related ARDS. Materials and Methods: The retrospectively planned study was performed in patients with COVID- 19-associated ARDS who were determined to have three phenotype subgroups based on the calculated static compliance (Cstat) value [type high (H) = Cstat <40 mL/cmH2O, type light (L) = Cstat ≥50 mL/cmH2O and type intermediate (Int) =40≤ Cstat <50 mL/cm H2O]. The effects of mechanical ventilation strategy on the duration of mechanical ventilation, length of stay in the intensive care unit, and mortality in COVID-19 ARDS phenotypes were investigated. Results: It was determined that the study patients were 72.3% type H, 23.4% type L, and 4.3% type Int in terms of COVID-19 ARDS phenotype. It was observed that the mechanical ventilation strategy did not affect the duration of mechanical ventilation (p=0.357), the length of stay in the intensive care unit (p=0.127), and the mortality rate (p=0.583) in all three phenotypes. Conclusion: We believe that a phenotype-independent protective ventilation strategy defined according to compliance is appropriate in patients with COVID-19-associated ARDS.